A new genus of gall midge (Diptera: Cecidomyiidae) inducing leaf galls on Rubus (Rosaceae). Issue 1 (27th February 2017) - Kolesik, Peter; Hall, Casey R; Kitching, Roger L; Adair, Robin J
Abstract: An undescribed species of gall midge causing hairy spheroidal leaf galls on Rubus nebulosus and Rubus moorei (Rosaceae) in subtropical Australia was investigated in a study on the dynamics of parasitoids of gall‐inducing insects. Here, the gall midge is described and named Psephodiplosis rubi Kolesik, sp. nov. in a new genus Psephodiplosis Kolesik, gen. nov. (supertribe Cecidomyiidi) erected to contain it. The new species is the first described gall midge that induces galls on Rosaceae in Australia. Similar galls have been found previously on Rubus moluccanus in Indonesia and on Rubus alceifolius in Thailand, so it is possible that the geographical range of Psephodiplosis rubi includes not only Australia, but also countries of South East Asia.